A new snow thermodynamic scheme for large-scale sea-ice models - Lecomte, Olivier; Fichefet, Thierry; Vancoppenolle, Martin; Nicolaus, Marcel (Annals of glaciology, 2011)
This paper assesses the capabilities of a new one-dimensional snow scheme developed for the thermodynamic component of the Louvain-la-Neuve sea-Ice Model (LIM). the model is validated at Point Barrow, Alaska, and at Ice Station Polarstern (ISPOL) in the western Weddell Sea, Southern Ocean. the new snow thermodynamic scheme leads to better snow internal temperature profiles, with a set-up-dependent increase in the correlation between simulated and observed temperature profiles. on average over all runs, these correlations are 27% better with the six-layer configuration. the model’s ability to reproduce observed temperatures improves with the number of snow layers, but stabilizes after a threshold layer number is reached. the lowest and highest values for this threshold are 3 (at Point Barrow) and 6 (at ISPOL), respectively. Overall, the improvement of the model’s ability to simulate sea-ice thickness is not as significant as for snow temperature, probably because of the rather crude representation of the snow stratigraphy in the model.